ANALISIS PENGELOLAAN PIUTANG KEPADA PERUSAHAAN ASURANSI KOMERSIAL DAN PERUSAHAAN REKANAN PADA RUMAH SAKIT BAPTIS BATU - Jessyca Phita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to analyze the management of commercial insurance companies and partner companies at the “Rumah Sakit Baptis Batu”. This research is a qualitative research with a descriptive approach. The data used are primary data in the form of interviews and secondary data in the form of accounts receivable claims from commercial insurance companies and partner companies. The results showed that the management of accounts receivable for inpatients and outpatients guarantees commercial insurance companies and partner companies are not in accordance with the accounting policies stated by the Baptist Hospital of Batu. The accounting policy states that receivables are stated at the net value that can be realized after being reduced by doubtful accounts. Nonbillable receivables are written off. Allowance for doubtful accounts is determined based on an individual review of each receivable balance at the end of the year. However, in reality the “Rumah Sakit Baptis Batu” does not make a list of accounts receivable ages and has not yet made a reserve for losses from receivables. Strategy how on solve the problem is by making a table listing the age of receivables and the percentage of receivable losses for each age group of receivables.Keywords: Account Receivables, Management of account receveibles, Evaluating of account receivable